1994
DOI: 10.1159/000236699
|View full text |Cite
|
Sign up to set email alerts
|

IgE-Specific Unresponsiveness in Mice Induced by Ovalbumin Coupled with Murine Red Blood Cells

Abstract: Ovalbumin (OVA) was coupled with murine red blood cells (MRBC) using glutaraldehyde. OVA-MRBC conjugate induced anti-OVA IgG antibody production in mice at almost the same level as OVA in alum. However, no IgE antibody production specific for OVA was observed in OVA-MRBC-injected mice. IgE-specifíc unresponsiveness was also observed in mice injected with OVA coupled with sheep red blood cells (OVA-SRBC), suggesting that our present observation was not restricted to the property of MRBC. These results show the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…OVA was coupled with liposomes in the same manner as the prep aration o f OVA-MRBC [4], Briefly, to 2 ml liposome solution, 0.5 ml o f 12 mg/ml OVA solution was added. Then 0.5 ml o f 2.4% GA solu tion was added dropwise to the mixture.…”
Section: Coupling O F Ova With Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…OVA was coupled with liposomes in the same manner as the prep aration o f OVA-MRBC [4], Briefly, to 2 ml liposome solution, 0.5 ml o f 12 mg/ml OVA solution was added. Then 0.5 ml o f 2.4% GA solu tion was added dropwise to the mixture.…”
Section: Coupling O F Ova With Liposomesmentioning
confidence: 99%
“…We have previously reported that an antigen coupled with red blood cells induced a significant IgG antibody production without IgE synthesis [4]. For the application of this system to practical use, liposomes were chosen for the coupling with antigens since they are biodegradable and are com posed of nontoxic and immunologically inert phospholipids that are common to all the mammalian cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of antigen-specific, IgE-selective unresponsiveness was first observed in mice immunized with antigens coupled to the surfaces of red blood cells (RBCs) (13). When ovalbumin (OVA) was coupled with murine RBCs (MRBCs) using glutaraldehyde (GA) and inoculated into mice, the OVA-MRBC conjugate induced anti-OVA IgG antibody production at almost the same level as OVA in alum.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum hydroxide (alum) has been widely used as an adjuvant for human vaccination and is well known to induce produc-tion of IgE antibody participating in allergic reaction (1). A number of attempts have been made to diminish IgE production while retaining its neutralizing activity, mainly associated with the IgG isotype (2)(3)(4). Alum is still in use, however, for various vaccines because it is effective as an adjuvant to induce protective antibodies, easy to handle, and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Purified preparations of diphtheria and tetanus toxoid used for coating the ELISA plates were kindly provided by the Research Foundation for Microbial Diseases, Osaka University, Osaka. Anti-diphtheria and anti-tetanus IgE antibodies were titrated by the passive cutaneous anaphylaxis (PCA) test in rats as described previously (4). In a preliminary experiment, a significant level of anti-diphtheria and antitetanus IgG production was observed as early as one week after ip injection of BALB/c mice with 0.5 ml of DPT-vaccine and the level reached plateau in 3 weeks.…”
Section: Discussionmentioning
confidence: 99%